Elevated Homocysteine: A Critical Risk Factor for Stroke Types and Subtypes – A Systematic Review and Meta-Analysis of 96 Studies - Manyata Srivastava; Annu Gulia; Pradeep Kumar (Acta Neurologica Taiwanica)
Background: The relationship between homocysteine (Hcy) levels and the risk of stroke has been extensively investigated, yet conclusive evidence remains elusive. Objectives: This study aims to conduct a systematic review and meta-analysis to determine the association between higher Hcy levels and the risk of stroke, including its types and subtypes. Materials and Methods: A comprehensive literature search was conducted in PubMed, MEDLINE, Google Scholar, EMBASE, and the Cochrane Library databases to identify relevant studies published up to April 30, 2024. We included case–control studies that examined the association of Hcy levels with risk of stroke and its types. Pooled standardized mean difference (SMD) with 95% confidence intervals (CIs), publication bias, trial sequential analysis (TSA), and quality assessment was conducted. Results: A total of 96 studies were included in the analysis: 83 studies on ischemic stroke (IS), 17 studies on Trial of ORG 10172 in Acute Stroke Treatment (TOAST) subtypes of IS, and 12 studies on hemorrhagic stroke (HS). The meta-analysis revealed a significant association between Hcy levels and risk of IS (SMD = 1.35, 95% CI = 1.14–1.55), TOAST subtypes of IS (SMD = 1.48, 95% CI = 1.03–1.92), and HS (SMD = 1.14, 95% CI = 0.68–1.59). TSA indicated that total sample sizes provided sufficient power (80%) to support findings: IS (n = 33,715), TOAST subtypes of IS (n = 5,655), and HS (n = 4,287). Conclusions: High Hcy levels are significantly associated with an increased risk of stroke, including its types and subtypes. These findings underscore the potential of Hcy as predictive marker for stroke risk. Future research should focus on strategies for detecting hyperhomocysteinemia and lowering elevated Hcy levels in high-risk individuals, which may contribute to stroke prevention.